Fractional Ostrowski Type Inequalities for Functions Whose Mixed Derivatives are Prequasiinvex and alpha-Prequasiinvex Functions - Badreddine Meftah; Meriem Merad; Abdourazek Souahi (Journal of the Indonesian Mathematical Society, 2019)
In this paper, the authors introduce two new classes of generalized convexfunctions of two independent variables, and establish a new integralidentity, from which they derive some new fractional Ostrowski's integralinequalities for functions whose second derivatives are in these new classesof functions.